The Icelandic Whooper Swan Cygnus cygnus population: current status and long-term (1986-2020) trends in its numbers and distribution - Brides, Kane; Wood, Kevin A.; Hall, Colette; Burke, Brian; McElwaine, Graham; Calbrade, Neil; Hill, Oisín; Rees, Eileen C.; Einarsson, Ólafur (Wildfowl, 2021)
The eighth international census of Whooper Swans Cygnus cygnus wintering in Britain, Ireland and Iceland (also including the Isle of Man and the Channel Islands) took place in January 2020, to update the estimates of the size, mid-winter distribution, habitat use and breeding success of the Icelandic Whooper Swan population. The total of 43,255 swans counted represented a 27.2% increase in numbers since the previous census in 2015. Overall, 36.8% of the population (15,927 birds) was recorded in England, 33.4% (14,467) in the Republic of Ireland, 11.7% (5,052) in Scotland, 10.7% (4,644) in Northern Ireland and 6.8% (2,923) in Iceland, with < 1% (242) in Wales, the Isle of Man and the Channel Islands combined. Despite numbers increasing in both the Republic of Ireland and Northern Ireland since 2015, the proportion of the total population in the Republic of Ireland was significantly lower in 2020 and no significant difference was detected for Northern Ireland, whereas proportions in England and Scotland were significantly higher in 2020 and lower in Iceland. Breeding success was not associated with temperatures on either the breeding or wintering grounds. It also showed no clear trend over time, suggesting that increased survival may be the demographic driver of the population growth.